Ask Question
15 October, 00:03

9 Which expression is equivalent to (2x - 5) -

(3x - 8)

A - x - 13

B - x + 3

C 2x - 16 D 5x - 3

0
Answers (2)
  1. 15 October, 00:34
    0
    Answer is - x+3

    2x-5 - (3x-8) distribute the negative sign

    = 2x-5+-1 (3x-8)

    = 2x + - 5 + - 1 (3x) + (-1) (-8)

    = 2x + - 5 + = - 3x + 8 combine like terms

    = (2x + - 3x) + (-5 + 8)

    = - x + 3
  2. 15 October, 01:54
    0
    I believe the answer is C or A
Know the Answer?
Not Sure About the Answer?
Get an answer to your question ✅ “9 Which expression is equivalent to (2x - 5) - (3x - 8) A - x - 13 B - x + 3 C 2x - 16 D 5x - 3 ...” in 📙 Mathematics if there is no answer or all answers are wrong, use a search bar and try to find the answer among similar questions.
Search for Other Answers